Historical Overview and Initiating Historiography of Islam in the Philippines - Thohir, Ajid (UIN Sunan Gunung Djati Bandung, 2015)
It will be more accurate to understand Islam in the Southeast Asia if the respective backgrounds of geo-political history are understood in particular. Western colonial influence such as Spanish, Portuguese, Dutch, English, French and United States that makes up the typology of Southeast Asian Islamic culture, strengthens the plurality of their Islamic character that seems increasingly clear. Philippine Muslim communities, that form the community of the Moro Islamic movement, are the products of the Spanish and the United States colonial policy, which determines the fate and treats Muslims as a conquered state. This long history results in the emergence of a heroic character in Philippines Muslims which is different from other Muslims in Southeast Asia that are relatively considered quiet and peaceful. Doing historiography of Islam in Southeast Asia without involving cases of Muslims in Philippines will not find the plurality of character.